A History of Mild Traumatic Brain Injury Affects Peripheral Pulse Oximetry during Normobaric Hypoxia - Temme, Leonard A.; St. Onge, Paul; Bleiberg, Joseph (Frontiers in Neurology, 2016)
Introduction: Physiological and emotional stressors increase symptoms of concussion in recently injured individuals and both forms of stress induce symptoms in people recovering from mild traumatic brain injury (mTBI) but who are asymptomatic when not stressed or are at rest. Methods: Healthy asymptomatic adults (25.0 ± 5.1 years) with a history of mTBI (n = 36) and matched healthy controls (n = 36) with no mTBI history were exposed to three levels of normobaric hypoxic stress generated with the Reduced Oxygen Breathing Device (ROBD) (Environics, Inc., Tollande, CT), which reduced the percent oxygen by mixing sea level air with nitrogen. The ROBD reduced the percent oxygen in the breathable air from the normal 21% to 15.5% O2, 14% O2, and 13% O2. Under these conditions: (a) a standard pulse oximeter recorded peripheral oxygen saturation (SpO2) and pulse rate (beats per minute), and (b) the FIT (PMI, Inc., Rockville, MD) recorded saccadic velocity and pupillary response dynamics to a brief light flash. Results: For all three hypoxic stress conditions the mTBI group had significantly higher SpO2 during the final minute of exposure than did the controls [F(2.17,151.8) = 5.29, p < .001, η2 = .852] and the rate of SpO2 change over time was significantly shallower for the mTBI than for the controls [F(2.3,161.3) = 2.863, p < .001, η2 = .569], Greenhouse-Geisser corrected. Overall, mTBI had lower pulse rate but the difference was only significant for the 14% O2 condition. FIT oculomotor measures were not sensitive to group differences. When exposed to mild or moderate normobaric hypoxic stress (15% O2): (1) SpO2 differences emerged between the mTBI and matched healthy controls, (2) heart rate trended lower in the mTBI group, and (3) FIT measures were not sensitive to group differences. Conclusion: A relatively minor hypoxic challenge can reveal measurable differences in SpO2 and heart rate in otherwise asymptomatic individuals with a history of mTBI.